ANALYTICAL CALCULATION OF PULLEY AND V-BELT FOR RICE THRESHER POWERED BY MATARI MGX-390 GASOLINE ENGINE - Faisal Rahman; Deri Teguh Santoso; Iwan Nugraha Gusniar; Jojo Sumarjo (Universitas Mercu Buana, 2022)
In the agricultural industry today, a lot of tools with automatic transmission have become primary needs for many people. To be able to operate a rice threshing machine, one that can support the running of the tool is the pulley and V-belt on the driving machine. Therefore, this research aims to analyze the pulley and V-belt on the rice thresher with the Matari MGX-390 gasoline engine so that it meets the required criteria and applicable standards. Due to the important role of the V-belt and pulley components, this study will discuss calculations in the design of V-belt and pulley components for a rice thresher with a Matari MGX-390 gasoline engine. The method used is direct observation, to see directly the shape and specifications of the rice thresher machine as well as the Matari MGX-390 gasoline engine used, also to record the dimensions of the pulley and V-belt so that further analysis is carried out on these components, and it can be seen whether the pulley and the V-belt used can be declared safe. Then calculations are carried out to determine the type of V-belt used, V-belt length, maximum voltage, demand voltage, and service life on the V-belt used. Based on the results of the research and calculations that have been carried out, it shows that the V-belt used by the rice thresher with the Matari MGX-390 machine can be declared safe with the type of V-belt used as type A, with a length of 1,649.74 mm, a maximum tension of 138.8 N, voltage requirement 121 N, service life 14,055 working hours.